Answer:
1. Ans;
[tex]f(x) = - 4(x + 1) \\ \\ f( - 4) = - 4( - 4 + 1) = - 4( - 3) = 12 \\ 8f( - 4) = 8(12) = 96 \\ \\ f(3) = - 4(3 + 1) = - 4(4) = - 16 \ \\ \\ \frac{8f( - 4)}{f(3)} = \frac{96}{ - 16} = - 6[/tex]
2. Ans;
[tex]f(x) = - 4(x + 1) \\ \\ f( - 13) = - 4( - 13 + 1) = - 4( - 12) = 48 \\ 3f( - 13) = 3(48) = 144 \\ \\ f(6) = - 4(6 + 1) = - 4(7) = - 28 \\ 5f(6) = 5( - 28) = - 140 \\ \\ 3f( - 13) + 5f(6) = 144 + ( - 140) \\ = 144 - 140 \\ = 4[/tex]
3.Ans;
[tex] f(x) = - 4(x + 1)\\ f(1) = - 4(1 + 1) = - 4(2) = - 8 \\ - 4f(1) = - 4( - 8) = 32 \\ \\ f( - 1) = - 4( - 1 + 1) = - 4(0) = 0 \\ 9f( - 1) = 9(0) = 0 \\ \\ - 4f(1) - 9f( - 1) = 32 - 0 = 32[/tex]
4.Ans;
[tex] f(x) = - 4(x + 1)\\ f(4) = - 4(4 + 1) = - 4(5) = - 20 \\ - 2f(4) = - 2( - 20) = 40 \\ \\ f( - 5) = - 4( - 5 + 1) = - 4( - 4) = 16 \\ \\ - 2f(4) \times f( - 5) = 40 \times 16 = 640 [/tex]
I hope I helped you^_^